Salivary biomarkers in oral squamous cell carcinoma - An insight - T. Radhika; Nadeem Jeddy; S. Nithya; R.M. Muthumeenakshi (Elsevier, 2016)
Oral cancer refers to the malignancies that occur in the oral cavity, lip and pharynx with 90% of oral cancers being squamous cell carcinomas (OSCC). OSCC has the highest mortality ratio compared to other carcinomas. Although oral cavity is easily accessible, most oral cancers are detected at a later stage leading to lower survival rates. Early detection of OSCC is a key factor in improving the prognosis and survival rate of the patient. Rapid advancement in the field of diagnosis has enabled early diagnosis of many potentially malignant conditions even before its clinical manifestations. One such diagnostic modality that has gained much relevance in the field of molecular biology has been the discovery of salivary biomarkers (DNA, RNA and protein markers). These salivary biomarkers have been shown to play a non-invasive role in the diagnosis and surveillance of oral cancer. The direct contact between the saliva and the oral cancer lesions makes it a most sensitive and specific, screening method in diagnosis, staging and follow-up. This review aims to discuss the effectiveness and the potential of salivary biomarkers as a screening tool in OSCC.